Cerdas & Aman di Dunia Digital : Pelatihan Keamanan dan Etika Bermedia Sosial - Fakhriani Ekawati; Lilis Anggraini; Muharir Muharir; Hayati Noor; Muhammad Amin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
In today’s digital era, the internet and social media have become an essential part of teenagers’ daily lives. Almost every day, they communicate, search for information, and share stories through various digital platforms. However, many are still unaware of how important it is to protect personal data and understand ethics when using social media. This lack of awareness often leads to problems, ranging from account misuse, the spread of hoaxes, to cases of online bullying that can harm many people.To address this issue, a training program was specifically designed for junior high school students to equip them with safe and responsible digital skills. The training not only provided theoretical explanations but also included real case simulations and hands-on practice so students could easily understand and apply the lessons. The materials covered simple ways to protect accounts, recognize signs of hoax news, and build healthy and positive interactions in the digital space.The results of the training showed that students became more aware of the importance of protecting privacy, more cautious before sharing information, and more respectful of ethics in every digital interaction. With a fun and practical approach, this program has proven effective in improving students’ digital literacy and fostering wise attitudes in using social media. In the future, such training is expected to be continuously implemented in schools as an effort to build a safer, healthier, and more cultured digital ecosystem